Getting to Know Patients’ Lived Space - Norlyk, Annelise (The Indo-Pacific journal of phenomenology, 2013)
The present paper explores patients’ experience of lived space at the hospital and at home. To expand the understanding of the existential meaning of lived space the study revisited two empirical studies and a study of a meta-synthesis on health and caring. Phenomenological philosophy was chosen as a theoretical framework for an excursive analysis. The paper demonstrates that existential dimensions of lived space at the hospital and at home differ significantly. For the patients, the hospital space means alien territory as opposed to the familiar territory of home. To some extent the experienced differences are due to the physical environment; however, as our analysis shows, other and more significant meanings are also involved. For patients, lived space at the hospital primarily concerns the influence of complex institutional power structures and specific cultural and social conventions, e.g. the role of the good patient and the ambiance of hospitals. Home, on the other hand, offers familiar lived space in which patients feel protected and safe. Further, the paper relates patients’ experience of lived space to a phenomenological view of lived space in order to illustrate the radical influence of illness on patients’ lifeworld and experience of lived space. The combination of illness and general discomfort may influence patients’ experience of home negatively; the former experience of home as a sanctuary changes into feelings of being left on one’s own and burdened by too much responsibility. Consequently, in the light of the increasing focus on patients’ self-monitoring at home, it is important for healthcare professionals to recognize the influence of spatial aspects on patients’ well-being both at the hospital and at home.